2016
DOI: 10.1590/1678-775720150445
|View full text |Cite
|
Sign up to set email alerts
|

Association of three putative periodontal pathogens with chronic periodontitis in Brazilian subjects

Abstract: Objective The aim of this study was to evaluate the association of Porphyromonas endodontalis, Filifactor alocis and Dialister pneumosintes with the occurrence of periodontitis.Material and Methods Thirty subjects with chronic periodontitis (ChP) and 10 with periodontal health (PH) were included in the study. Nine subgingival biofilm samples were collected as follows: i) PH group - from the mesial/buccal aspect of each tooth in two randomly chosen contralateral quadrants; ii) ChP group - from three sites in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…and Prevotella sp. It is important to note that the microbial profile of our study population was in agreement with previous studies that found higher levels of these bacterial species in the subgingival biofilm of subjects with periodontitis [26][27][28] and no differences were observed between our data and the data provided by the literature. However, it is important to highlight that our study population presented a clinical profile compatible with mild periodontitis, and we also found a complex microbiota in their subgingival biofilm.…”
Section: Discussionsupporting
confidence: 91%
“…and Prevotella sp. It is important to note that the microbial profile of our study population was in agreement with previous studies that found higher levels of these bacterial species in the subgingival biofilm of subjects with periodontitis [26][27][28] and no differences were observed between our data and the data provided by the literature. However, it is important to highlight that our study population presented a clinical profile compatible with mild periodontitis, and we also found a complex microbiota in their subgingival biofilm.…”
Section: Discussionsupporting
confidence: 91%
“…Real‐time quantitative PCR (qPCR) has been used as an approach to rapidly quantify specific periodontal pathogens (Masunaga et al, 2010). In addition to real‐time qPCR, other DNA‐based techniques being used in assessing the oral bacteria include checkerboard hybridization (Dahlen et al, 2016; Goncalves et al, 2016; Vieira Colombo et al, 2016). This technique compared with a real‐time qPCR is more labor intensive and time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of checkerboard hybridization is the detection limit that requires the presence of about 10 4 to 10 6 bacterial cells in most samples (Brito et al, 2007). However, with this approach, the presence of a larger microbial population can be analyzed simultaneously (Dahlen et al, 2016; Goncalves et al, 2016; Vieira Colombo et al, 2016). The benefits of a real‐time qPCR, on the other hand, are that it offers a sensitive means of detecting and quantifying small number of bacteria in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several species belonging to different complexes have been associated with periodontal health, in particular those from the genera Actinomyces , Streptococcus and Capnocytophaga . It is also important to note that there is moderate evidence in the literature to support the existence of newly identified periodontal pathogens or host‐compatible species but the role of these species as true pathogens or as markers for periodontal stability are yet to be established, especially by risk assessment and interventional studies. Therefore, the 40 bacterial species defined by Socransky et al .…”
Section: Introductionmentioning
confidence: 99%